An Investigator Led Clinical Trial in Practice Showing the Efficacy of Tamsulosin and Silodosin as Medical Expulsive Therapy in the Management of Distal Ureteral Stones: A Case Study in Urology - A. S. Albert; Santosh R. Pillai; Anila Mary; Rajeev Aravindakshan (Perspective of Recent Advances in Medical Research Vol. 12, 2023)
Alpha blockers are being commonly used as adjuvants in the medical management for the expulsion of ureteral stones. The present randomized study aims to evaluate the efficacy of Tamsulosin and Silodosin as medical therapy in the management of symptomatic distal ureteral stones. Methods: In this randomized control study the 120 patients enrolled were allotted to three groups. Patients in group 1 received tablet Tamsulosin 0.4 mg/day, group 2 received tablet Silodosin 8mg/day and group 3 served as the control group. Parameters noted were the blood pressure, stone position (% of expulsion in each group), adverse events noted and number of hospital visits. All patients were followed up weekly for a period of 28 days. Results: Study showed that both Tamsulosin (80% success) and Silodosin (85 %success rate) are equally efficacious when compared to the control group. Group 1 and Group 2 required less of pain killers and also had less frequent hospital admissions due to painful episodes as compared to the control group. Usual adverse reaction seen with alpha blockers like orthostatic hypotension and retrograde ejaculation were reported by some subjects in the test groups. Conclusions: Both the drugs appear to be effective in the medical management of distal ureteral stones.ButTamsulosin scores over Silodosin as it’s well tolerated and with good stone expulsion rates.